NEC4 : 100 questions and answers - Hughes, Kelvin (Engineering consultant) (Abingdon, Oxon ; New York, NY : Routledge, 2019)
This book details some of the most important and interesting questions raised about the NEC4 family of contracts and provides clear, comprehensive answers to those questions. Written by an NEC expert with over 20 years' experience using, advising and training others, the book has several distinctive features: It covers the whole NEC4 family It is written by a very experienced NEC author who explains sometimes complex issues in a simple and accessible style The questions and answers range from beginner level up to a masterclass level The questions are real life questions asked by actual NEC practitioners on real projects. The book includes questions and answers relating to tendering, early warnings, programme issues, quality management, payment provisions, compensation events, liabilities, insurances, adjudication, termination and much more. It is essential reading for anyone working with the NEC4 family of contracts, whether professionals or students in construction, architecture, project management and engineering.
Introduction to the nec4 contracts -- Early warnings and risk registers -- Contractor's design -- Time and the accepted programme -- Quality management -- Payment provisions -- Managing compensation events -- Title -- Indemnity, insurance and liability -- Termination provisions -- Dealing with disputes -- Preparing and assessing tenders.
OCLC-licensed vendor bibliographic record.
Keywords: NEC4.; Construction contracts -- Great Britain -- Miscellanea; Civil engineering contracts -- Great Britain -- Miscellanea; ARCHITECTURE / Professional Practice; ARCHITECTURE / Project Management; LAW / Construction